2017
DOI: 10.1186/s13643-017-0602-8
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes-related information-seeking behaviour: a systematic review

Abstract: BackgroundInformation-seeking behaviour is necessary to improve knowledge on diabetes therapy and complications. Combined with other self-management skills and autonomous handling of the disease, it is essential for achieving treatment targets. However, a systematic review addressing this topic is lacking. The aims of this systematic review were to identify and analyse existing knowledge of information-seeking behaviour: (1) types information-seeking behaviour, (2) information sources, (3) the content of searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 48 publications
6
61
0
1
Order By: Relevance
“…One systematic review found that older adults and adolescents alike prefer online media as their source for information on diabetes, although patients with diabetes wanted the online information to be verified by their medical expert (e.g. GP or dietitians) [96]. Not all elderly people have the necessary skills to use digital technologies.…”
Section: Evidence-based Communication Strategiesmentioning
confidence: 99%
“…One systematic review found that older adults and adolescents alike prefer online media as their source for information on diabetes, although patients with diabetes wanted the online information to be verified by their medical expert (e.g. GP or dietitians) [96]. Not all elderly people have the necessary skills to use digital technologies.…”
Section: Evidence-based Communication Strategiesmentioning
confidence: 99%
“…Therefore, considering the rapidly growing number of online health users, it is of great significance to understand the key factors of online health information-seeking behavior, which is valued by most scholars for improving users' healthcare. According to information behavior models, the main categories of intervening variables of online health information-seeking behavior (OHISB) include psychological factors, demographic factors, role-related or interpersonal factors and environmental factors [4,5]. Therefore, the key factors, including 17 variables in this meta-analysis, are classified into four parts based on this categorization method.…”
Section: Introductionmentioning
confidence: 99%
“…The first part is the demographic characteristic variables, which involve age, education, income, and gender. The second part refers to cognitive factors, which are defined by the users making decisions based on the perception of things and reflect users cognitive and emotional characteristics, as mentioned in previous studies, including perceived usefulness, perceived ease of use, perceived behavioral control, perceived risk, perceived benefit and perceived cost [5]. The third category is internal factors that reflect the impact of differences in individual characteristics of consumers on OHISB, containing self-efficacy, attitude, Internet experience, health anxiety, and trust.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing searching is "where active searching has already established the basic framework of knowledge, but where occasional continuing search is carried out to update or expand one's framework" (pg 3). Passive attention is where "information acquisition may take place without intentional seeking" (pg 3) (29). We selected Wilson's model over other models of information behaviour as it offered a broad summary of the context of the information need of the seeker, the type of searching employed and the information sources utilised, and was not focused on the information seeking process.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%